Horse Games and Entertainment - Bekmirzaev Rakhmonali Begalievich; Ilebayev Arstanbek Kasenovich; Yoldoshev Salimjon Valiyevich (Genius Journals, 2023)
This article provides information about the ancient equestrian games of the Kyrgyz. The origin and features of equestrian games are analyzed.
Keywords: Kyrgyz; nomadism; nomadic lifestyle